Morphometries of Emiliania huxleyi in the Pacific sector of the XX Italian Expedition from New Zealand to Antarctic - Mariem Saavedra-Pellitero; Elisa Malinverno; Karl-Heinz Baumann; Nele Manon Vollmar; Nuria Bachiller-Jareno; Harold Lovell (PANGAEA, 2025)
This micropalaeontological dataset includes morphometries of the extant coccolithophore species Emiliania huxleyi in two transects in the Pacific sector of the Southern Ocean (from New Zealand to Antarctica and across the Drake Passage). The New Zealand transect: 13 selected surface water samples were collected from the ship extquotesingles pump of the R/V Italica (at ca. 3 m water depth) from 46.81°S to 62.49°S during the XX Italian Expedition from New Zealand to Antarctica (31st December 2004- 6th January 2005). In total, 377 coccoliths of E. huxleyi were classified and measured using Scanning Electron Microscope (SEM) images.